We are all aware of the generating function of $\frac{x \arctan x}{x^2+1}$ which is:

$$\frac{x \arctan x}{x^2+1} = \sum_{m=1}^{\infty} (-1)^m \left ( \mathcal{H}_{2m} - \frac{1}{2} \mathcal{H}_m \right ) x^{2m} \tag{1}$$

Now, integrating both sides, we get that:

$$\sum_{m=1}^{\infty} \frac{(-1)^m \mathcal{H}_{2m} }{2m+1} - \frac{1}{2} \sum_{m=1}^{\infty} \frac{(-1)^m \mathcal{H}_m}{2m+1} = \frac{\mathcal{G}}{2} - \frac{\pi \log 2}{8}$$

I do not present the calculations here of the integral , but is suffices to say that is elementary. Apply IBP and then it boils down to the integral $\int_0^{\pi/4} \log \cos x \, {\rm d}x$ which is quite known.

My question is if we can evaluate those Euler sums individually. As hard as I searched I could not find to what these two

$$\sum_{m=1}^{\infty} \mathcal{H}_{2m}x^{2m} \quad, \quad \sum_{m=1}^{\infty} \mathcal{H}_m x^{2m}$$

both converge to. I remember seeing something for the second sum , but sadly I have not kept record of the result. But never have I encountered something for the first one. I guess they are going to have closed forms.



For all $|z|<1$:

$\displaystyle A(z):=\sum_{n=1}^{+\infty} H_{2n}z^{2n}$

It's well known that:

For all $|z|<1$:

$\displaystyle F(z):=\sum_{n=1}^{+\infty} H_nz^n=-\dfrac{\ln(1-z)}{1-z}$

$\displaystyle F(z)=\sum_{n=1}^{+\infty} H_{2n}z^{2n}+\sum_{n=0}^{+\infty} H_{2n+1}z^{2n+1}$

$\displaystyle G(z):=\sum_{n=0}^{+\infty} H_{2n+1}z^{2n+1}=z+\sum_{n=1}^{+\infty}\left(H_{2n}+\dfrac{1}{2n+1}\right)z^{2n+1}$

$\displaystyle G(z)=z+zA(z)+\sum_{n=1}^{+\infty}\dfrac{z^{2n+1}}{2n+1}$

$\displaystyle G(z)=zA(z)+\sum_{n=0}^{+\infty}\dfrac{z^{2n+1}}{2n+1}$

For $|z|<1$,

$\displaystyle \sum_{n=0}^{+\infty}\dfrac{z^{2n+1}}{2n+1}=\dfrac{1}{2}\ln(1+z)-\dfrac{1}{2}\ln(1-z)$

For $|z|<1$, derivative of the left member is:

$\displaystyle \sum_{n=0}^{+\infty}z^{2n}=\dfrac{1}{1-z^2}=\dfrac{1}{2}\dfrac{1}{1-z}+\dfrac{1}{2}\dfrac{1}{1+z}$

Therefore, for $|z|<1$,


Finally, for $|z|<1$,



for $|z|<1$,

$\displaystyle \sum_{n=1}^{+\infty} H_nz^{2n}=F(z^2)=-\dfrac{\ln(1-z^2)}{1-z^2}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.